Related Party Transactions, Off Balance Sheet Items and Earnings Quality of Listed Deposit Money Banks in Nigeria (Malaysian Management Journal, 2019)
This paper examines the impact of related party transactions, off balance sheet items on earnings quality of listed deposit money banks in Nigeria over the period of 4 years (2011 to 2014). Data were collected from annual reports of the sampled banks. Descriptive statistics and correlation analysis were employed and also Ordinary least square (OLS) robust regression technique was used as a tool of analysis using panel data. The study reveals that related party transactions are positively and significantly related to earnings quality. On the contrary, off balance sheet items were found to be negatively and insignificantly related to earnings quality. Based on the findings, the study concluded that related party transactions have significant impact on the earnings quality of the Nigeria deposit money bank. The study recommends that Management of the Nigeria money deposit banks should be more aggressive towards the number of genuine related party transactions that can add value to their firms when making financial decision because it is likely to have positive effects on the quality of their earnings.